Genome-wide screening of sex-biased genetic variants potentially associated with COVID-19 hospitalization - Luo, Yu-Si; Li, Wei; Cai, Yi; Zhang, Jingxuan; Gui, Hongsheng; Zhang, Ke; Cheng, Zhong-Shan (Frontiers in Genetics, 2022)
Sex-biased difference in coronavirus disease 2019 (COVID-19) hospitalization has been observed as that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected male patients tend to be more likely to be hospitalized than female patients. However, due to the insufficient sample size and existed researches that more prioritized to sex-stratified COVID-19 GWAS, the searching for sex-biased genetic variants showing differential association signals between sexes with COVID-19 hospitalization was severely hindered. We hypothesized genetic variants would be potentially sex-biased genetic effects on COVID-19 hospitalization if they display significant differential association effect sizes between male and female COVID-19 patients. By integrating two COVID-19 GWASs, including hospitalized COVID-19 patients vs. general population separated into males (case = 1,917 and control = 221,174) and females (case = 1,343 and control = 262,886), we differentiated the association effect sizes of each common single nucleotide polymorphisms (SNPs) within the two GWASs. 12 SNPs were suggested to show differential COVID-19 associations between sexes. Further investigation of genes (n = 58) close to these 12 SNPs resulted in the identification of 34 genes demonstrating sex-biased differential expression in at least one GTEx tissue. Finally, five SNPs are mapped to eight genes, including rs1134004 (GADD45G), rs140657166 (TRIM29 and PVRL1), rs148143613 (KNDC1 and STK32C), rs2443615 (PGAP2 and TRIM21), and rs2924725 (CSMD1), and these 8 genes display significantly differential gene expression in blood samples derived from COVID-19 patients compared to healthy controls. These genes are potential genetic factors contributing to sex differences in COVID-19 hospitalization and warranted for further functional studies.